Regarding "Let's Get It Started" (Summer 2006) - Stevan Harnad (Issues in Science and Technology Librarianship, 2006)
A letter to the editor by Stevan Harnad is presented in response to the article "Let's Get It Started," by George S. Porter in the Summer 2006 issue. This letter comments on challenges to self-archiving in institutional repositories, including creating institutional repository software, library activism and research impact of self-archiving.